PECULIARITIES OF DEVELOPING A STRATEGY FOR THE DEVELOPMENT OF TOURISM ENTREPRENEURSHIP ENTITIES OF TERRITORIAL COMMUNITIES - Малярчук, Наталія; Подзіґун, Світлана (Modern engineering and innovative technologies, 2022)
At the current stage, to start any business, it is necessary to think strategically. In general, a similar business approach is just as appropriate to choose for the formation and promotion of the tourist brand of the territorial community, because touris